Multilingual Realities and English Teacher Construction in Indonesian Pesantren: A Narrative Inquiry - Ahmad Madkur (CV. Creative Tugu Pena, 2024)
This study aimed to explore the construction of English teacher identity within the multilingual and religiously oriented environment of Indonesian pesantren through a narrative inquiry approach. Applying narrative inquiry, the study examined how teachers negotiate their religious and professional identities while balancing multiple language ideologies embodied in this educational context. Data were collected through in-depth semi-structured interviews and reflective journals, providing rich narratives of teachers' experiences, challenges, and strategies in navigating their roles. Three key themes emerged: balancing language ideologies, the interplay between religious and professional identities, and multilingual practices in the classroom. The findings reveal the dynamic, context-responsive nature of teacher identity development within pesantren, highlighting how educators align religious values with pedagogical goals. This study addresses a critical gap by focusing on identity formation in faith-based multilingual education settings, offering new insights beyond secular or formal institutions. The implications contribute to broader discussions on teacher identity, multilingual education, and the intersection of language, religion, and teaching practices.